Pain neuroscience education for the management of chronic pain in elite volleyball players with chronic shoulder pain: a randomized controlled trial - Koç, H.; Dengiz, A. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background The aim of this study was to examine the effects of pain neuroscience education (PNE) on pain intensity, pain knowledge, and pain catastrophizing in elite volleyball players with chronic shoulder pain.